2002
DOI: 10.1177/103841620201100208
|View full text |Cite
|
Sign up to set email alerts
|

An Exercise to Improve Career Understanding of Commencing Engineering and Technology Students

Abstract: The literature suggests that many commencing engineering students do not have an accurate understanding of the nature of professional practice in their chosen career. Many of the methods for exposing students to professional practice are impractical for large classes of commencing students. An assessment activity involving students collecting job advertisements for professional engineering positions and analysing them for required skills and knowledge was trialed and evaluated. It was found that a significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Such outcomes assist students to more rationally explore and choose their courses of study and relevant graduate employment options. For example, career development learning has been used to foster 1 st -year undergraduate engineering students' engagement with their studies by assisting them to explore their decision to enter the discipline (Palmer & Bray, 2002); and it has been used to better prepare final-year students for the world-ofwork by teaching them skills in self-assessment of employability in relation to current demands in the employment market (Graham, 1999;McIlveen & Gibson, 2000). Folsom and Reardon's (2003) review of 38 empirical studies, conducted over a 25-year period, found evidence of positive effects upon: (i) job satisfaction, (ii) selecting a degree major, (iii) course satisfaction, (iv) retention and graduation rates, and (v) grade-point average.…”
Section: Engagement With Studiesmentioning
confidence: 99%
“…Such outcomes assist students to more rationally explore and choose their courses of study and relevant graduate employment options. For example, career development learning has been used to foster 1 st -year undergraduate engineering students' engagement with their studies by assisting them to explore their decision to enter the discipline (Palmer & Bray, 2002); and it has been used to better prepare final-year students for the world-ofwork by teaching them skills in self-assessment of employability in relation to current demands in the employment market (Graham, 1999;McIlveen & Gibson, 2000). Folsom and Reardon's (2003) review of 38 empirical studies, conducted over a 25-year period, found evidence of positive effects upon: (i) job satisfaction, (ii) selecting a degree major, (iii) course satisfaction, (iv) retention and graduation rates, and (v) grade-point average.…”
Section: Engagement With Studiesmentioning
confidence: 99%
“…Career services have developed industry‐specific initiatives, such as: providing career education to engineering students to consolidate their career understanding, commitment to study, and learning how to demonstrate their employability skills in the workplace (McIlveen and Gibson, 2000; Palmer and Bray, 2002) and in e‐portfolios (McCowan et al , 2005). In reflecting a dimension of social justice in their practices (e.g.…”
Section: Career Services Within Australian Higher Educationmentioning
confidence: 99%
“…Career Services have developed industry-specific initiatives, such as: providing career education to engineering students to consolidate their career understanding, commitment to study, and learning how to demonstrate their employability skills in the workplace (McIlveen & Gibson, 2000;Palmer & Bray, 2002) and in e-portfolios (McCowan, Harper, & Hauville, 2005). In reflecting a dimension of social justice in their practices (e.g., McIlveen, Everton, & Clarke, 2005), Career Services have also attended to the needs of students who experience difficulties in the transition to the workforce: for example, students with a disability (McIlveen, Cameron, McLachlan, & Gunn, 2005); international students unfamiliar with cultural nuances (Smith, Grainger, Lacey, & Bassett, 2007); and arts and humanities students whose disciplines lack a definitive professional skill set (Lewis & Ruchel, 1993;Waugh, 1993).…”
Section: Career Services Within Australian Higher Educationmentioning
confidence: 99%